Relationship between the Coronary Slow Flow Phenomenon and the Vertebrobasilar Insufficiency - Yasin Yüksel; Cennet Yildiz; İbrahim Taşkın Rakici; Cansu Erkol; Fatma Nihan Turhan Çağlar (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2025)
Background: Coronary slow flow phenomenon (CSFP) and vertebrobasilar insufficiency (VBI) may have common pathophysiological mechanism. Aim: Our aim was to investigate whether there is an association between vertebrobasilar flow assessed by Doppler sonography and CSFP assessed by Thrombolysis in Myocardial Infarction (TIMI) frame count. Methods: We included 241 patients who had CSFP and underwent vertebrobasilar Doppler sonography. Patients with vertebral artery blood flow volumes greater than 200 ml/min and equal to or less than 200 ml/min were classified into the normal flow and low flow groups, respectively. Hospital records were used to determine the biochemical and demographic characteristics of the patients. Results: The mean age of the study population was 58.75±9.34 years. We found no differences between patients with normal and low vertebral blood flow in terms of age, sex, body mass index, smoking habit, presence of hypertension, hyperlipidemia, diabetes mellitus or medication use. Patients with low vertebral blood flow were found to have greater mean platelet volume. The mean TIMI frame count and LAD, Cx, and RCA TIMI frame counts were significantly greater in patients with low vertebral blood flow and were negatively correlated with the vertebral artery blood flow volume (p<0.001 for all). A mean TIMI frame count of 24.5 predicted VBI, with a sensitivity and specificity of 61.2% and 86.8%, respectively. The only predictor of VBI was the mean TIMI frame count (OR: 1.066, 95% confidence interval: 1.043–1.091, P<0.001). Conclusion: Our findings suggest that a common pathophysiological mechanism may underlie both CSFP and VBI.